2022
DOI: 10.3389/fpls.2022.898307
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genome-Wide Identification and Expression Profiling of Eceriferum (CER) Gene Family in Passion Fruit (Passiflora edulis) Under Fusarium kyushuense and Drought Stress Conditions

Abstract: Plant surfaces are covered with cuticle wax and are the first barrier between a plant and environmental stresses. Eceriferum (CER) is an important gene family involved in wax biosynthesis and stress resistance. In this study, for the first time, 34 CER genes were identified in the passion fruit (Passiflora edulis) genome, and PeCER proteins varied in physicochemical properties. A phylogenetic tree was constructed and divided into seven clades to identify the evolutionary relationship with other plant species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 131 publications
2
13
0
Order By: Relevance
“…The fruit's wax content was greater in the HT group compared to the control group in this study, which is associated with the expression of genes related to wax synthesis and transport. CER genes are likely related to fruit cuticle, in particular, biosynthesis of waxe (Rizwan et al., 2022). Belge et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fruit's wax content was greater in the HT group compared to the control group in this study, which is associated with the expression of genes related to wax synthesis and transport. CER genes are likely related to fruit cuticle, in particular, biosynthesis of waxe (Rizwan et al., 2022). Belge et al.…”
Section: Resultsmentioning
confidence: 99%
“…The fruit's wax content was greater in the HT group compared to the control group in this study, which is associated with the expression of genes related to wax synthesis and transport. CER genes are likely related to fruit cuticle, in particular, biosynthesis of waxe (Rizwan et al, 2022). Belge et al (2019) employed heat shocks to treat peaches and observed that heat shocks restored the expression of the PpLACS1 gene (also known as CER8), which is involved in n-alkane biosynthesis from fatty acyl-CoAs (Von Wettstein-Knowles, 2016).…”
Section: 23mentioning
confidence: 99%
“…The CER gene family contributes to the production of cuticle wax and has a vital function in stress mitigation [ 12 ]. The CER gene family has been found across the genome in a range of plant species, including Castanea mollissima [ 32 ], apple [ 29 ] and passion fruit ( Passiflora edulis ) [ 31 ], and functionally described in (A) thaliana [ 43 ], Barley [ 44 ], Brachypodium distachyon [ 45 ], and (B) napus [ 46 ]. However, the CER genes in cotton ( G. hirsutum ) have not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies in the exons and introns number represent a significant source of diversity in gene families, influencing gene function and expression [ 52 ]. In this study, CER genes were found to have quite different numbers of introns, ranging from 3 to 13 introns, which is less than passion fruit (1–28) [ 31 ], and sunflower (1–19) [ 30 ]. The GaCER09 gene has a lower number of introns (2), while GaCER08 contains 11 introns.…”
Section: Discussionmentioning
confidence: 99%
“…It was not until 2021 that a chromosome-scale genome assembly of passion fruit (Passiflora edulis Sims) was just reported (Xia et al, 2021). This work enables several documentations for the identification of passion fruit genes, including eceriferm (CER), aquaporin (AQP), β-Ketoacyl-CoA synthase (KCS), peroxidase (POD), lateral organ boundary domain (LBD), and lipoxygenase (LOX) gene families (Rizwan et al, 2022a;Song et al, 2022;Rizwan et al, 2022b;Liang D. et al, 2022;Liang J. et al, 2022;Huang et al, 2022). However, one of the major barriers in gene functional studies is the lack of a simple and efficient transformation system in passion fruit.…”
Section: Introductionmentioning
confidence: 93%